From “Nostalgia for Classic” to “The End of Classic as Nostalgia”: Winckelmann and Burckhardt - Acosta, María del Rosario (Estudios de Filosofía, 2005)
This text proposes to answer a question about the relation between Aesthetics and Philosophy of History as found in the Aesthetic Theories of Winckelmann (half of the XVIIIth Century) as opposed to Burckhardt's reflexions on History (end ofthe XIXth Century), and each ofthese is crossed by the meaning the concept of “classic” acquires in them. The idea is to show how a History of Art such as Winckelman's, whose criterion is Greek Art as canon, necessarily entails with it a Philosophy of History that supports it and makes it possible; at the same time, that a reflexion about History such as Burckhardt's, that presents itself as an answer to the Neo-classic tradition and to the Romantic tradition that comes right before it, displays behind it an Aesthetic Thought that is self-made.